Pendidikan Agama Islam di Tengah Tantangan Sekularisasi dan Liberalisasi Pendidikan - Mubayanah Tawabie, Siti; Hasanah; Qaribilla, Roys (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
In the educational context, secularization refers to the separation of religious values from the formal education system. This process is often associated with a reduction in the role of religion in the school curriculum, which places more emphasis on scientific and rational aspects. On the other hand, educational liberalization gives schools more freedom to create their own learning programs, and often ignores moral and spiritual aspects. This phenomenon can cause students to lose religious principles, which can result in loss of identity and a decline in moral quality. Therefore, this research aims to learn more about how the challenges of secularization and liberalization affect PAI and the solutions that can be used to maintain its relevance.